The efficacy of Lifebuoy and Safeguard a comparative study - Mendoza, Michael Antonio F.
Dental treatment must be done with adequate infection control procedures. Handwashing with a cleansing agent is accomplished to reduce and hinder bacterial colonization. The aim of the study is to compare the efficacy of two commercially-available germicidal soap bars, Lifebuoy? and Safeguard?, as a pre-operative handwash through quantitative assay. The imprint of the index finger of the non-working hand will be recorded in a blood-agar culture media for culturing prior to visual counting of colony-forming units (CFU). Thirty (30) subjects were distributed to two (2) groups after baseline data collection, each corresponding to a specimen soap bar. Soap A resulted to a mean of 3.57 CFU, while Soap B had a mean of 3.86 CFU. The mean CFU of the two groups were statistically compared through t-ratio testing. Though one soap resulted to a more mean CFU decrease, the difference is not statistically significant to conclude that one soap is better than the other. This meant that Lifebuoy? and Safeguard? have comparable efficacy as germicidal soaps.